Epithelioid Hemangioendothelioma with WWTR1-CAMTA1 Fusion in the Parotid Gland Presenting as Bell’s Palsy - Landon J. Kunzelman; Shweta Agarwal; Nathan Boyd; Cory J. Broehm (Case Reports in Pathology)
Epithelioid hemangioendothelioma is a rare tumor of endothelial differentiation most commonly arising in soft tissue, liver, and lung, following a variable clinical course. Most cases are characterized by a t(1;3)(p36;q23-25) resulting in WWTR1-CAMTA1 fusion. Only five epithelioid hemangioendothelioma have been previously reported arising in the salivary glands. None have presented as Bell’s palsy. In the current case, a 37-year-old female presented with a longstanding complaint of pain and fullness in the right preauricular region and progressive episodes of Bell’s palsy and facial nerve weakness. Surgical resection showed a tumor comprised of atypical cells with occasional intracytoplasmic vacuoles in a fibromyxoid stroma. Immunohistochemical stains demonstrated the neoplastic cells expressed ERG, CD31, and CD34, confirming vascular differentiation. Fluorescence in situ hybridization revealed a t(1;3)(p36;q25), confirming a diagnosis of epithelioid hemangioendothelioma. At 12-month follow-up, the patient has no evidence of disease.